Conception of spherical triangle in terms of learning styles - Ari Sriantini; Mega Teguh Budiarto; Yusuf Fuad (STKIP PGRI Banjarmasin, 2020)
This study aims to describe the conception of students in the material of spherical triangle in terms of learning styles. The conception of the students described based on the identification of students to spherical triangle and implementation spherical triangle to determine the distance of the ship and the course. Student representations of spherical triangles focused on calculating the parts of spherical triangles, the use of spherical rules for calculating distance and course of ships on a voyage. This research is an exploratory study with a qualitative approach. The subjects of this study were first semester students of the Nautica Program who have visual, auditory, and kinesthetic learning styles. The results showed that there were differences in conceptions between students who had visual, auditory, and kinesthetic learning styles. Lecturers are expected to have the right strategy in delivering lecture material, so that the material can be easily understood by students who have different learning styles.